Augmented Reality User Interface: Analysing the Design Principles and Evaluation Methods of Augmented Reality (AR) User Interfaces to Enhance User Interaction and Experience - Liu, Ziyu (International Journal of Computer Science and Information Technology, 2024)
This article investigates user interface design and evaluation methods for augmented reality (AR) systems and analyses existing problems. The article begins with an overview of AR technology, and then explores the principles of traditional interface design and the guiding principles of AR user interface design and their limitations. Then, user experience evaluation and AR user interface evaluation methods are outlined. Through literature search and screening, the article finds that there is a lack of universal standard AR design and evaluation guidelines. The article also discusses the relationship between traditional interface design and evaluation principles and AR interface design and evaluation principles, and points out that more in-depth research and exploration of new evaluation methods are needed in the future to further expand the library of evaluation tools for specific AR studies.